Cephalometric Variables Influencing Soft Tissue Profile Beauty in Pakistani Population. - Saleem, Huma; Faisal, Syed Shah; Hussain, Syed Sheeraz (International Medical Journal, 2023)
Objective: To determine cephalometric factors influencing soft tissue profile beauty in Pakistanis and assess if the soft tissue values of Ricketts, Holdaway, and Merrifield analyses for Caucasians differ from those of attractive Pakistani profiles. Design: Cross-sectional study Materials and Methods: The study population included 45 subjects with normal occlusion and symmetric faces. Their lateral cephalograms were converted to black and white silhouettes, which were then ranked based on their attractiveness by a group of 30 laypeople. On the 12 profiles judged as aesthetically pleasing, Ricketts, Holdaway, and Merrifield analyses were performed. The Caucasian orthodontic norms were compared with the attractive group using a 1-sample t-test, taking a p-value of < 0.05 as significant. Results: The attractive group had significantly greater H angle (P = 0.001), skeletal profile convexity (P = 0.002), and superior sulcus depth (P = 0.041), while nose prominence (P = 0.000), Z angle (P = 0.000), and total chin thickness (P = 0.002) were less than the Caucasian norms. Conclusions: This study showed a preference for Ricketts' lip projection values in Pakistanis. Additionally, the study population showed significant differences from the orthodontic norms proposed in Holdaway's and Merrifield's analyses.